Gender, Occupation, Family Support and Self Care Behavior in Diabetes Mellitus Patients - Endang Widiawati; Dewi Hartinah; Ashri Maulida Rahmawati (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
It is estimated that cases of diabetes mellitus will continue to increase between 2030 and 2045. To prevent serious complications, good self-care behavior is essential, including maintaining a balanced diet, engaging in physical activity, conducting regular blood sugar checks, consistently taking medication, practicing proper foot care, and avoiding smoking. The purpose of this study was to determine the relationship between gender, age, and family support with self-care behavior among diabetes mellitus patients at A Kudus Health Center. This research used a correlational analytic method with a cross-sectional approach. The sample consisted of 61 respondents selected through purposive sampling.The data collection instruments included a demographic questionnaire, the Hensarling Diabetes Family Support Scale (HDFSS), and the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire—all of which had been tested for validity and reliability. Data were analyzed using univariate and bivariate analyses, with the Spearman rank correlation test.The results showed a significant relationship between family support and self-care behavior among diabetes mellitus patients (p = 0.003; p < 0.05). However, there was no correlation between gender, occupation, and self-care behavior with p value; > 0.05. .